Majority-Minority Relations in a Multicultural Society: The Case of Switzerland - Schmid, Carol L. (My University, 1978)
Switzerland, a country which has managed to weld four different language groups and two major religions into a harmonious unity has long been a major enigma in an age of cultural nationalism. Currently it is one of the few national communities without a shared culture whose overall political unity is not threatened. This work attempts to trace major sources of Swiss coexistence as well as some of the problems now facing Switzerland. Because most of the literature in race and ethnic relations has focused on causes of conflict and discord, majority-minority relations in Switzerland has received relatively little attention. The first part of the study investigates various attempts to explain the Swiss case. Explanations such as cross-cutting cleavages and the politics of consociational democracy are given special attention. The hypothesis of cross-cutting cleavages, which currently represents the dominant explanation of Swiss coexistence, says in essence that cross-cutting cleavages such as religion, language, etc., tend to create cross-pressures among the population that serve to moderate the intensity of political conflict. While this view helps explain the stability and cohesion of the Swiss polity it is shown to be overly simplistic and reductionist. Another major explanation is that of consociational democracy. Although it, too, contributes to our understanding of Swiss harmony, by emphasizing the conscious and deliberate efforts of autonomous elites it neglects the role of popular sentiment and public opinion. This study focuses on the transmission of values, and the relationship between public opinion and attitudes and cores values in a multicultural setting. In order to explore the salience of popular sentiment and public opinion in contributing to Swiss coexistence, an analysis of Swiss history textbooks from French and German, Catholic and Protestant Switzerland was carried out. It was found that in contrast to Canada and South Africa, the school curriculum tends to unite rather than divide the various cultural groups by de-emphasizing those historical themes which feed intergroup resentment. Even though the authors present various interpretations of some events, there is an underlying consensus of what the Swiss state should stand for. In addition, the textbooks promote a positive sense of Swiss identity which transcends a narrow linguistic or cultural definition of nationhood. A survey administered to French and German Swiss youth reinforces this interpretation. A variety of indicators show that the German Swiss who comprise three-fourths of the population lack what may be called a "majoritarian outlook". While the opposite is not q completely true of the French Swiss minority, they do not display that sense of relative deprivation that is often associated with sociological minorities. When asked why they were proud to be Swiss, both French- and German-speaking youth gave political answers considerably more often than any other reasons. Thus, there appears to exist "a certain Swiss outlook" which unites the Swiss cultural and linguistic groups. This does not mean that Switzerland has solved all problems of a cultural and ethnic nature. The Jura question and the foreign worker problem remain two problematic issues in the conduct of majority-minority relations in Switzerland. A solution to the Jura situation now seems to be in sight. In contrast, the foreign worker problem which involves a non-national minority remains unresolved. This points to the fact that Swiss policy toward non-citizen minorities is at variance with the treatment of citizen minorities. In concluding this study we propose an important corollary to pluralist thought which posits an implicit correlation between social heterogeneity and political instability. Our basic proposition is that a "civic culture", moderates social conflicts and promotes stability in multicultural settings.
Keywords: Sociology; Sociology